Innovation and Technology in Table Tennis - Chareerat Udomvirojsin; Suppawan Vongsrangsap (Universitas Negeri Semarang (UNNES) in cooperation with ACPES (ASEAN Council of Physical Education and Sport), 2023)
The advancement of innovation and technology has been seen in table tennis for many years; for example, developing the racket design with the innovation to make its weight lighter for better control, using the innovation for training in the form of robot to enhance the player’s reaction, accuracy and footwork. Moreover, a variety of technologies can help broaden the player’s skills to make the game more exciting and challenging as well as to gain more experience for entertainment in every level.The innovation and technology in table tennis has been still developed gradually, especially seeking for something new to facilitate the player’s training such as the robot available for playing interaction with the player, innovation for data analysis to clarify the information for performance improvement, and technology for experience promotion with playing simulation program, etc.It can be said that nowadays innovation and technology have a significant effect on table tennis, particularly transformation from an indoor sport to a high – tech game for better experience of interested persons. In the future it is expected that innovation and technology will create a challenge in various forms and enable everyone to reach the game in various convenient ways.